2016
DOI: 10.1007/s11999-015-4559-4
|View full text |Cite
|
Sign up to set email alerts
|

Does Strict Adherence to the Ponseti Method Improve Isolated Clubfoot Treatment Outcomes? A Two-institution Review

Abstract: Background Despite being recognized as the gold standard in isolated clubfoot treatment, the Ponseti casting method has yielded variable results. Few studies have directly compared common predictors of treatment failure between institutions with high versus low failure rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 32 publications
(45 reference statements)
2
24
0
2
Order By: Relevance
“…The PM was perceived to be effective yielding better clinical results improving the functional prognosis of the condition in a shorter period. This is consistent with other studies [ 15 , 29 , 30 ]. It is suggested that with good technique the clubfoot should be corrected in two months with weekly castings [ 17 ].…”
Section: Discussionsupporting
confidence: 94%
“…The PM was perceived to be effective yielding better clinical results improving the functional prognosis of the condition in a shorter period. This is consistent with other studies [ 15 , 29 , 30 ]. It is suggested that with good technique the clubfoot should be corrected in two months with weekly castings [ 17 ].…”
Section: Discussionsupporting
confidence: 94%
“…In our institution, clubfoot treatment was managed by a single surgeon (Z.L.) with rigid adherence to the Ponseti method such that treatment technique was consistent and the data were comparable 16 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the Ponseti method has received increasing attention in the treatment of clubfoot and has become the most commonly used method. Although the success rate of Ponseti's first correction is satisfactory after a long period of development, there are still many problems and challenges, such as having a recurrence of deformity, having a poor compliance, and determining the best time to stop wearing braces (Miller et al, 2016;Thacker et al, 2005).…”
Section: Introductionmentioning
confidence: 99%